A 22 Billion M⊙ Black Hole in Holmberg 15A with Keck KCWI Spectroscopy and Triaxial Orbit Modeling - Emily R. Liepold; Chung-Pei Ma; Jonelle L. Walsh (The Astrophysical Journal, 2025)
Holmberg 15A (H15A), the brightest cluster galaxy of A85, has an exceptionally low central surface brightness even among local massive elliptical galaxies with distinct stellar cores, making it exceedingly challenging to obtain high-quality spectroscopy to detect a supermassive black hole (SMBH) at its center. Aided by the superb sensitivity and efficiency of KCWI at the Keck II Telescope, we have obtained spatially resolved stellar kinematics over a ∼100″ × 100″ contiguous field of H15A for this purpose. The velocity field exhibits a low-amplitude (∼20 km s ^−1 ) rotation along a kinematic axis that is prominently misaligned from the photometric major axis, a strong indicator that H15A is triaxially shaped with unequal lengths for the three principal axes. Using 2500 observed kinematic constraints, we perform extensive calculations of stellar orbits with the triaxial Schwarzschild code, TriOS, and search over ∼40,000 galaxy models to simultaneously determine the mass and intrinsic 3D shape parameters of H15A. We determine a ratio of p = 0.89 for the middle-to-long principal axes and q = 0.65 for the short-to-long principal axes. Our best estimate of the SMBH mass, ${M}_{{\rm{BH}}}=(2.1{6}_{-0.18}^{+0.23})× 1{0}^{10}{M}_{\odot }$ , makes H15A—along with NGC 4889—the galaxy hosting the most massive SMBHs known in the local Universe. Both SMBHs lie significantly above the mean M _BH – σ scaling relation. Repeating the orbit modeling with the axisymmetrized version of TriOS produces worse fits to the KCWI kinematics and increases M _BH to (2.55 ± 0.20) × 10 ^10 M _⊙ , which is still significantly below the M _BH = (4.0 ± 0.8) × 10 ^10 M _⊙ reported in a prior axisymmetric study of H15A.